Differential Contributions of MYCs to Insect Defense Reveals Flavonoids Alleviating Growth Inhibition Caused by Wounding in Arabidopsis - Wang, Dan-Dan; Li, Pai; Chen, Qiu-Yi; Chen, Xue-Ying; Yan, Zi-Wei; Wang, Mu-Yang; Mao, Ying-Bo (Frontiers in Plant Science, 2021)
In Arabidopsis, basic helix–loop–helix transcription factors (TFs) MYC2, MYC3, and MYC4 are involved in many biological processes, such as defense against insects. We found that despite functional redundancy, MYC-related mutants displayed different resistance to cotton bollworm (Helicoverpa armigera). To screen out the most likely genes involved in defense against insects, we analyzed the correlation of gene expression with cotton bollworm resistance in wild-type (WT) and MYC-related mutants. In total, the expression of 94 genes in untreated plants and 545 genes in wounded plants were strongly correlated with insect resistance, and these genes were defined as MGAIs (MYC-related genes against insects). MYC3 had the greatest impact on the total expression of MGAIs. Gene ontology (GO) analysis revealed that besides the biosynthesis pathway of glucosinolates (GLSs), MGAIs, which are well-known defense compounds, were also enriched in flavonoid biosynthesis. Moreover, MYC3 dominantly affected the gene expression of flavonoid biosynthesis. Weighted gene co-expression network analysis (WGCNA) revealed that AAE18, which is involved in activating auxin precursor 2,4-dichlorophenoxybutyric acid (2,4-DB) and two other auxin response genes, was highly co-expressed with flavonoid biosynthesis genes. With wounding treatment, the WT plants exhibited better growth performance than chalcone synthase (CHS), which was defective in flavonoid biosynthesis. The data demonstrated dominant contributions of MYC3 to cotton bollworm resistance and imply that flavonoids might alleviate the growth inhibition caused by wounding in Arabidopsis.